Homozygous deficiency of the second component of complement presenting with recurrent bacterial meningitis. Issue 6 (June 1980) - Thong, Y H; Simpson, D A; Müller-Eberhard, H J
Abstract : A girl presented with purulent meningitis at ages 6, 8, and 11 years. She was in good health between these three episodes. When aged 16 one of her brothers also experienced an attack of pneumococcal meningitis. Complement studies showed lack of C2 in the patient and the brother, and intermediate values in the mother and a sister. No other member of the family was available for study.